Analisis Kebijakan dan Strategi CSR Sebagai Bagian dari Planning Development - Muhammad Edy Susilo; Prayudi Ahmad (CHANNEL: Jurnal Komunikasi, 2020)
Corporate Social Responsibility is a business concept that is increasingly being adopted in Indonesia. However, there are many variations of CSR implemented. An oil and gas company is a company whose operations have a large impact on the surrounding environment. This paper is the result of research from the CSR activities of oil and gas companies operating close to residential areas. The research problem statement is how the implemented CSR strategy goes hand in hand with the company's overall policy? Is the CSR program being carried out following what is needed by the community? The theory used is the theory of stakeholders who are the people and organizations that influence the company's activities. The results showed that CSR activities carried out had passed the processual stages, namely the selection of stakeholders, social mapping, selection of priorities and programs, implementation, and evaluation. The company has placed CSR as an important form of social investment in the long term.